Empleo y crecimiento urbano : aplicación del modelo de Czamanski al caso mexicano - Verduzco Chávez, Basilio (El Colegio de México A.C., 1991)
This article consists in the application of Czamanski's model, which is based on the theories of urban growth and industrial localization, in order to ellaborate a clasification of activities at the branch level according to the factors explaining their presence in a given city. The advantages of this model in its application as a support instrument in the process of urban planning when the information available is incomplete are also discussed as well as the model's usefulness in analysing the process of urban growth in Mexico. For this purpose we constructed a census data base on 44 cities including all the metropolitan areas of Mexico and the majority of the main urban areas in the State of Jalisco and the Western region of the country.